2000
DOI: 10.1017/s0033822200059075
|View full text |Cite
|
Sign up to set email alerts
|

Radiocarbon Reservoir Ages in the Mediterranean Sea and Black Sea

Abstract: We measured apparent marine radiocarbon ages for the Mediterranean Sea, Black Sea, and Red Sea by accelerator mass spectrometry radiocarbon analyses of 26 modern, pre-bomb mollusk shells collected living between AD 1837 and 1950. The marine reservoir (R(t)) ages were estimated at some 390 ± 85 yr BP, 415 ± 90 yr BP and 440 ± 40 yr BP, respectively. R(t) ages in the Mediterranean Sea and Black Sea are comparable to those for the North Atlantic Ocean (<65°N), in accordance with the modern oceanic circulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
253
0
6

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 342 publications
(273 citation statements)
references
References 27 publications
14
253
0
6
Order By: Relevance
“…14 C ages were also obtained on a series of Holocene mollusk shells sampled at different depths of the ~8-m-long core PB06. Careful examination of the 14 C ages versus depth relationships suggests that R(t) in the past was lower and similar to the value presently measured in the Gulf of Lion (618 ± 30 14 C yr, Siani et al 2000). The change in R(t) from 618 to 943 yr is thought to result from final closure of the coastal lagoon by the sandy barrier, due to the along-shore sediment transfer.…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…14 C ages were also obtained on a series of Holocene mollusk shells sampled at different depths of the ~8-m-long core PB06. Careful examination of the 14 C ages versus depth relationships suggests that R(t) in the past was lower and similar to the value presently measured in the Gulf of Lion (618 ± 30 14 C yr, Siani et al 2000). The change in R(t) from 618 to 943 yr is thought to result from final closure of the coastal lagoon by the sandy barrier, due to the along-shore sediment transfer.…”
Section: Introductionsupporting
confidence: 63%
“…For the central part of the Gulf of Lion, Siani et al (2000) found a higher R estimated at 245 ± 30 yr (R(t)  618 ± 30 14 C yr), which is the average of 3 samples collected at Sète and Banyuls and recalculated by using the calibration model of Hughen et al (2004). This offset from the Marine04 model has been explained as a result of biological processes or hardwater effects due to the discharge of coastal rivers after dissolution of limestone via several brackish lagoons, before reaching this part of the Mediterranean Sea.…”
Section: Modern Reservoir Age Estimationmentioning
confidence: 99%
“…The chronology of the two cores retrieved from Dhaka and Maya MVs (TTR17-MS411G and TTR17-MS419G, respectively) is based on 8 AMS 14 C ages ( (Siani et al, 2000) was subtracted to the obtained radiocarbon conventional ages, which were calibrated using the program Calib 5.1 (Stuiver and Reimer, 1993).…”
Section: Methodsmentioning
confidence: 99%
“…Calibration using the software Calib 5.1 (Stuiver and Reimer, 1993). A reservoir effect of 400 years was subtracted (Siani et al, 2000). G. inflata increases from 45 cm upwards to over 30% in the upper part of the core with a negative peak (10%) at 35 cm.…”
Section: Quantitative and Statistical Analysesmentioning
confidence: 99%
“…PGM/MIS 6: Astakhov, 2011Astakhov et al, 2016;Ehlers et al, 2011a, b;Gurski et al, 1990;Mohr, 1993;Rose, 2009;Rose et al, 2002, Ruzicka, 2004Velichko et al, 2011. 2003a,b). d 18 O records include data for the surface-dwelling planktonic foraminifer Globigerinoides ruber (white) for all cores, and for the subsurface-dwelling planktonic foraminifer Neogloboquadrina pachyderma (dextral) for core LC21 (habitats after Rohling et al, 2004), and we use conversions to sea level after Rohling et al (2014) Grant et al, 2012;Hennekam, 2015), and recalibrating original 14 C datings with the most recent 14 C calibration curve (Reimer et al, 2013) using a DR value of 35 ± 70 years (Siani et al, 2000).…”
Section: Denton and Hughes 2002mentioning
confidence: 99%